Traditional Passive Design Solutions as a Key Factor for Sustainable Modern Urban Designs in the Hot, Arid Climate of the United Arab Emirates - Salameh, Muna (2022)
Sustainable architecture is a key approach for creating sustainable cities and reducing the impact of climate change. In hot, arid regions, the passive design traditional architecture is known for its ability to provide comfortable indoor environments and outdoor shaded areas, in contrast to the use of energy-intensive air conditioners in a great deal of modern architecture. Thus, this research used a qualitative methodology based on ENVI-met software to study, investigate, and compare the thermal performance of two urban fabrics as case studies (traditional and modern districts) in the hot, arid climate of the United Arab Emirates. The thermal performance of the old urban districts was better than the new ones, with a lower maximum potential air temperature and an improvement in the level of thermal comfort, measured by a predicted mean vote. Moreover, it was found that enhancing the shade in the outdoor open areas in the modern district, mimicking the traditional passive design solutions, resulted in lower air temperature and PMVs. This research is expected to be one step among many towards creating sustainable, innovative modern architecture.